Supplementation of Sakura Block Plus in Beef Cattle Fed with Palm Fronds and Its Effect on Nutrient Digestibility - jarmuji, jarmuji; Badarina, Irma; Warly, Lili (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Sakura Block Plus is a modification of Sakura Block, incorporating 6% earthworms and palm kernel cake as substitutes for corn. The objective of this study was to evaluate the supplementation of Sakura Block Plus in palm frond feed on the nutrient digestibility of beef cattle. The research design employed a Latin Square Design (LSD) with treatments P0 (10% Sakura Block Plus), P1 (8% Sakura Block Plus), P2 (10% Sakura Block Plus), and P3 (12% Sakura Block Plus). Four male beef cattle, 18 months old, weighing approximately ± 110 kg, were utilized throughout four treatment periods, each lasting 15 days. The results of the study indicated a significant improvement in the 12% Sakura Block Plus treatment concerning the digestibility of Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), and hemicellulose. In conclusion, the supplementation of Sakura Block Plus at the 12% level in palm frond feed resulted in the most optimal nutrient digestibility.